A paradiplomacia como instrumento viabilizador do desenvolvimento local: estudo de caso a partir da atuação internacional do estado de pernambuco e da cidade do recife - Siqueira, João Ricardo Pessoa Xavier de (2012)
The contemporary international scenario, outlined by the paradigm of globalization, is characterized by the admission of new players that can articulate themselves in an interdependent manner. Inserted in the wide range which consists the group of these new players, are subnational governments and their international articulation models that characterize the phenomenon of paradiplomacy. Among the objectives that guided the research, we tried to approach the paradiplomatic phenomenon as a result of changes in the prevailing world order, characterizing it as an effect of the subnational actors‟ behavior in face to the new governance standards. Furthermore, paradiplomacy was framed up as a viable institute for the development of the Brazilian federation‟s constituent units. Therefore, the work was based on a case study with descriptive-analytical character that had as objects of observation the state of Pernambuco and the city of Recife, with their respective models of international insertion and articulation. We took as guiding theoretical referential the literature already produced in the area consisting primarily on the studies by Soldatos, Paquin, Lecours and Prieto. In the present study it was possible to set up the analysis on the efficacy of paradiplomatic activity on two levels: state and municipal through paradiplomacy performed by the two subnational governments already mentioned via autonomous agencies.